Political Participation of Civil Society Organizations in Salvador - Borges, Jussara (2012)
For the majority of citizens political participation in democracy requires just voting in periodical elections. However, this comprehension of participation has been pressed by theorists that defend the development of democracy by the deepening of citizens participation and by the increase of public service deficiency to satisfy social needs. Innovative participative practices, which challenge established concepts, have been more and more present in the performance of civil society organizations. On the other hand, social organizations have become privileged spaces to discuss and support public interest objectives. This paper discusses the ways social organizations of Salvador (BA, Brazil) participate politically. The methodology encompassed interviews with 44 organizations. The main results show that: (i) the observation of social organizations political participation requires new patterns of analysis to overcome traditional factors as “electoral participation”, “party identification” and “reliance in institutions”; (ii) the new patterns of analysis must aggregate new actors to those factors; (iii) among the main forms of participation there are those lined up to the concepts of the so called deliberative democracy, as, for example, the valorization of public debates; (iv) there are changes in the political participation ways of these organizations, mainly in the sense of the development and the variety they express themselves.